2022
DOI: 10.3389/fneur.2022.897454
|View full text |Cite
|
Sign up to set email alerts
|

Central sensorimotor integration assessment reveals deficits in standing balance control in people with chronic mild traumatic brain injury

Abstract: Imbalance is common following mild Traumatic Brain Injury (mTBI) and can persist months after the initial injury. To determine if mTBI subjects with chronic imbalance differed from healthy age- and sex-matched controls (HCs) we used both the Central SensoriMotor Integration (CSMI) test, which evaluates sensory integration, time delay, and motor activation properties and the standard Sensory Organization Test (SOT). Four CSMI conditions evoked center-of-mass sway in response to: surface tilts with eyes closed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…The motor activation parameters characterize the transformation from the internal sensory-derived estimate of body orientation and motion to the corrective ankle torque needed to resist gravity and stabilize upright stance. These parameters can affect the sensitivity of sway responses to internal and external perturbations to balance ( 25 ). For both parameters, post-hoc comparisons showed significant differences between the VS /EO and SS/EO condition as well as between the VS /EO and SS/EC ones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The motor activation parameters characterize the transformation from the internal sensory-derived estimate of body orientation and motion to the corrective ankle torque needed to resist gravity and stabilize upright stance. These parameters can affect the sensitivity of sway responses to internal and external perturbations to balance ( 25 ). For both parameters, post-hoc comparisons showed significant differences between the VS /EO and SS/EO condition as well as between the VS /EO and SS/EC ones.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study investigating postural deficits in people with chronic mild traumatic brain injury ( 25 ) showed that sensitivity was affected by both sensory weights and by the stiffness factor Kp . In the current study, although mean Kp did not differ between groups there was still variation in Kp within each group that would be expected to influence an individual’s stimulus-evoked sway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered long-latency trans-cortical responses may be influenced by an inability to appropriately prime a stepping response before the release 31 or an inappropriate motor responses, driven by altered sensory integration and state estimation, after a loss of balance. 14,32 However, such conclusions remain speculative and further research is needed to uncover the mechanisms underlying concussion-related reactive balance impairments.…”
Section: Discussionmentioning
confidence: 99%
“…By analogy to standing balance control, body sway variability can arise from sensory, motor, and central processing noise sources but is also influenced by the dynamic properties of the overall control system ( 84 , 85 ). While spontaneous sway variability during stance provides some indication of overall balance system behavior, the application of external perturbations and the use of system identification methods that are appropriate for control systems where feedback plays a major role ( 86 ) can enhance our ability to identify which components of the system are responsible for balance deficits ( 87 ).…”
Section: Discussionmentioning
confidence: 99%